A PMMA-based heterogeneous photocatalyst for visible light-promoted [4 + 2] cycloaddition. Issue 7 (9th March 2020) - Huber, Niklas; Li, Run; Ferguson, Calum T. J.; Gehrig, Dominik W.; Ramanan, Charusheela; Blom, Paul W. M.; Landfester, Katharina; Zhang, Kai A. I.
Abstract : Macromolecular organic photocatalysts consisting of a PMMA network with integrated conjugated moiety have broad and promising applications in visible light-promoted photoredox catalysis. Abstract : Macromolecular organic photocatalysts consisting of a completely conjugated network have broad and promising applications in visible light-promoted photoredox catalysis. Precise reproduction and control of exact conjugation length remains an important challenge for fully conjugated and macromolecular photocatalysts. Here, we introduce a new photocatalytic material based on classical PMMA copolymerised with defined electron donor and acceptor units with precisely controllable redox potential and conjugation length, creating a promising class of metal-free, stable and low-cost heterogeneous photocatalysts. Furthermore, swelling of the PMMA copolymer matrix in organic solvents led to enhanced substrate diffusion and thereby increased catalytic efficiency. High efficiency and selectivity was achieved for photocatalytic [4 + 2] cycloaddition reactions in air with low effective photocatalyst loading. The photocatalytic efficiency of the PMMA photocatalyst was comparable with the state-of-the-art metal or non-metal catalysts while facilitating easy recyclability.